Vaccine Development Against Tuberculosis Over the Last 140 Years: Failure as Part of Success - Kaufmann, Stefan H. E. (Frontiers in Microbiology, 2021)
The year 2020 was shaped by the COVID-19 pandemic which killed more people than any other infectious disease in this particular year. At the same time, the development of highly efficacious COVID-19 vaccines within less than a year raises hope that this threat can be tamed in the near future. For the last 200 years, the agent of tuberculosis (TB) has been the worst killer amongst all pathogens. Although a vaccine has been available for 100 years, TB remains a substantial threat. The TB vaccine, Bacille Calmette-Guérin (BCG), has saved tens of millions of lives since its deployment. It was the best and only choice available amongst many attempts to develop efficacious vaccines and all competitors, be they subunit vaccines, viable vaccines or killed whole cell vaccines have failed. Yet, BCG is insufficient. The last decades have witnessed a reawakening of novel vaccine approaches based on deeper insights into immunity underlying TB and BCG immunization. In addition, technical advances in molecular genetics and the design of viral vectors and adjuvants have facilitated TB vaccine development. This treatise discusses firstly early TB vaccine developments leading to BCG as the sole preventive measure which stood the test of time, but failed to significantly contribute to TB control and secondly more recent attempts to develop novel vaccines are described that focus on the genetically modified BCG-based vaccine VPM1002, which has become the frontrunner amongst viable TB vaccine candidates. It is hoped that highly efficacious vaccines against TB will become available even though it remains unclear whether and when this ambition can be accomplished. None the less it is clear that the goal of reducing TB morbidity and mortality by 90% or 95%, respectively, by 2030 as proposed by the World Health Organization depends significantly on better vaccines.